Effects of Tamarillo (Solanum betaceum) Extract on Glutathione Peroxidase Expression and Inflammatory Reactions in Lead Acetate-Induced Lung Tissue of Mice - Harjono, Shella; I’tishom, Reny; Rahniayu, Alphania; Fatimah, Nurmawati (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Lead acetate exposure through oral route has a significant impact on lung tissue as lead can induces the formation of reactive oxygen species (ROS), resulting in decreased glutathione peroxidase (GPx) and triggering inflammatory responses. The induction of exogenous antioxidants may prevent this mechanism. This study aimed to evaluate the protective effect of Tamarillo ethanol extract on GPx expression and inflammatory reactions in the lung tissue of mice induced with lead acetate.Methods: This true experimental laboratory study utilized stored formalin-fixed-paraffin-embedded (FFPE) lung tissue from 30 male mice (Mus musculus). The samples were divided into five intervention groups, each consisting of six mice. Immunohistochemistry and histopathology assessments were performed at 100x and 400x magnification to evaluate the GPx expression using the H-score and to assess inflammatory reactions based on five scoring parameters, which were summed to obtain the total lung injury score.Results: Lead exposure significantly increased inflammatory reactions, particularly in the hemorrhage parameters (p=0.041). A significant increase in GPx expression was observed following lead acetate administration (p=0.027). Administration of Tamarillo ethanol extract at a dose of 400 mg/kgBW increased GPx expression compared with the positive control group (p=0.027).Conclusion: Tamarillo ethanol extract, especially at a dose of 400 mg/kgBW, significantly increases GPx expression in lead acetate-induced lung tissue of mice. This finding highlights the potential role of Tamarillo extract as an antioxidant source to reduce lead-induced lung injury, supporting broader efforts to promote healthy lifestyle practices that protect against environmental toxin exposure.